Subjectivity of Chinese fansub: Autonomy placed under structural pressures - Xu, Minghua; Deng, Boyi (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2023)
Since the digitisation of the early 21st century, the Chinese fansubs, who are spontaneously enthusiastic about translating the captions of foreign movies and TV dramas, have re-emerged as a topic of interest among researchers due to changing Chinese social contexts. This article aims at examining the relationship between politically driven technique and Chinese fansubs. Through a netnographic study, we explore the technical logic, the paradox of subjectivity, and the evolving nature of these virtual communities. Our argument suggests that the fansub phenomenon can contribute to our understanding of digital labour, whether in the form of organized teams or individual efforts.